A critical analysis of the enforcement of the right to access to adequate housing in South Africa - Mudzielwana, Takalani (My University, 2023)
The South African constitution 1996 provides for the fundamental human rights that must be enjoyed by all within its borders. This includes section 26 of the Constitution, which gives everyone the right to adequate housing regardless of economic status. Thus, more emphasis is placed on previously marginalised population groups. However, due to corruption, high inequality gap between the poor and rich, and limited financial resources, many people do not have adequate housing. This study examined how well the South African government is upholding this right. It will go into more detail about the potential outcomes of the constitutional framework, the judicial system, and other relevant institutions. This study further analyses the effectiveness of the South African government in promoting, implementation and fulfilling the right to adequate housing. Different laws, policies, legislation, and initiatives by the government to fulfil and protect people’s right of access to adequate housing are reviewed and assessed. Also, the fulfilment of the adequate housing right is interrelated to other rights like water, electricity, food, education, and healthcare. The study examined the effectiveness of the execution of the need for affordable housing in South Africa.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2023
Keywords: Human rights; Legislations; Policies; Adequate housing; South African constitution; Housing policy -- South Africa; Human rights -- South Africa; Housing -- Law and legislation -- South Africa; Constitutional law -- South Africa